Peningkatan Kreativitas Pemecahan Masalah melalui Metode Team Product pada Mahasiswa PGSD Universitas Sarjanawiyata Tamansiswa - Lilis Diah Kusumawati; Christina Ismaniati; Trisniawati Trisniawati (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study is to improve the creativity of problem solving through the method of team product on the 2nd grade students Prodi S1 PGSD University Sarjanawiyata Tamansiswa (UST). Classroom action research is conducted in two cycles, and each cycle has two meetings with planning, action, observation and reflection. Data collection using test and nontest techniques. Data were analyzed using quantitative and qualitative descriptive statistical analysis. The results showed that compared with pretest result before using team product method and after use of team product method, there is an increase of learning result from pretest to posttest of cycle I as much as 4% then increase 4% again in cycle II. Overall for the average pretest is 70.5 then the posttest average value after the action done on the first cycle that is equal to 75.1 and continues to increase to 78.8 in cycle II.